Innovating public service delivery in Germany: What drives digital transformation at the local level? - Liz Marla Wehmeier; Philipp Gräfe (International Review of Administrative Sciences, 2026)
Digital transformation is widely seen as a key dimension of public sector innovation, expected to reshape and improve service delivery. Yet, empirical developments often fall short of these expectations, particularly in local and decentralised public administrations. We employ a mixed methods design to investigate the state of digitalisation and implementation dynamics in selected areas of German public administration and to identify key drivers shaping substantive digital transformation. Specifically, we employ qualitative interview data ( n = 64) and quantitative survey data ( n = 1751) from three digitally mature administrative domains: vehicle registration; building permitting; and tax administration. The findings show that despite high ambitions, digital transformation remains fragmented, with persistent deficits such as the parallelism of paper-based and digital procedures and limited back-office digitalisation. Internal drivers, such as leadership, dedicated personnel and employee involvement, prove crucial for achieving substantive digital transformation. Points to practitioners This study highlights the central role of internal drivers in shaping meaningful public sector digitalisation. Local administrators should: ‐ prioritise back-office digitalisation; ‐ establish dedicated organisational structures for digitalisation within departments, such as a digitalisation unit; and ‐ actively involve staff through training and change management initiatives.